An introduction to foreign exchange (London : Euromoney Publications PLC, 1983)
The programme covers topics such as spot rates, indication rates, direct and indirect quotes, dealer information services, currency exposure, forward rates, settlement instructions and premiums & discount.
Copy available in DVD format
Keywords: Foreign exchange